2004
DOI: 10.1128/jvi.78.16.8573-8581.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Stable Retroviral Transduction and Cell Survival following DNA Integration Depend on Components of the Nonhomologous End Joining Repair Pathway

Abstract: Integration of viral DNA into host DNA is an essential step in the replication cycle of retroviruses and retrotransposons (4, 13, 26). The first two steps in this process, viral DNA processing and joining, are catalyzed by the retroviral protein integrase and require specific sequences at the ends of the viral DNA. In the first step, nucleotides (usually two) are removed from the 3Ј ends of the viral DNA, and in the second step, these newly created ends are joined to staggered phosphates in the complementary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 27 publications
5
97
0
Order By: Relevance
“…The Scid mutation may confer a restricted LV-transduction to MEFs [19,20], hence leading to a specific defective reprogramming of Scid cells. To investigate whether a reduced transduction efficacy was accounting for the restricted ability of Prkdc scid MEFs for being reprogrammed, wt and Scid MEFs were transduced with multiplicities of infection (MOIs) of 5 and 10 transduction units (TUs) per cell using the STEMCCA-RedLight LV.…”
Section: Resultsmentioning
confidence: 99%
“…The Scid mutation may confer a restricted LV-transduction to MEFs [19,20], hence leading to a specific defective reprogramming of Scid cells. To investigate whether a reduced transduction efficacy was accounting for the restricted ability of Prkdc scid MEFs for being reprogrammed, wt and Scid MEFs were transduced with multiplicities of infection (MOIs) of 5 and 10 transduction units (TUs) per cell using the STEMCCA-RedLight LV.…”
Section: Resultsmentioning
confidence: 99%
“…a human immunodeficiency virus type 1 (HIV-1) vector). However, these and subsequent studies 21,22 showed that the death of NHEJ-deficient cells was, in fact, dependent on the presence of active integrase in the infecting virion. Based on these results, it was proposed that retroviral DNA integration is perceived by cells as DNA damage, and that failure in postintegration repair triggers apoptosis in NHEJ-deficient cells ( Figure 5).…”
Section: Evidence That Retroviral Postintegration Repair Depends On Hmentioning
confidence: 99%
“…Using this Figure 5 Model for the role of DNA damage sensing, NHEJ, and an alternative pathway in postintegration repair approach, it was shown that the efficiency of retroviral transduction of human and rodent cell that are deficient in NHEJ is only 10-20% of that observed with controls. [20][21][22] Given the cell killing described above, reduced transduction efficiency is most readily explained as a result of apoptosis following abortive integration in these NHEJ repair-deficient cells. Consistent with this interpretation, wortmannin was found to reduce the efficiency of retroviral transduction of HeLa cells infected with ASV or HIV-1 vectors, with dose dependence that correlated with reduction of DNA-dependent protein kinase activity in these cells.…”
Section: Evidence That Retroviral Postintegration Repair Depends On Hmentioning
confidence: 99%
“…The induction of a cellular response similar to DNAdamage-sensing signals has been shown during human immunodeficiency virus type-1 (HIV-1) infection (Daniel et al, 1999(Daniel et al, , 2003(Daniel et al, , 2004Lau et al, 2004). The synthesis of linear HIV-1 DNA in the cytoplasm by reverse transcription and the integration process of HIV-1 DNA into the host genome are thought to be possible triggers for the DNA-damage signals (Lau et al, 2004(Lau et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%